2018
DOI: 10.1016/j.spl.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

New and refined bounds for expected maxima of fractional Brownian motion

Abstract: For the fractional Brownian motion B H with the Hurst parameter value H in (0,1/2), we derive new upper and lower bounds for the difference between the expectations of the maximum of B H over [0,1] and the maximum of B H over the discrete set of values in −1 , i = 1, . . . , n. We use these results to improve our earlier upper bounds for the expectation of the maximum of B H over [0, 1] and derive new upper bounds for Pickands' constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Thus, most of the work is focused on finding upper and lower bounds for these quantities (see, e.g. [35,12,10,4,7,8,5]) or determining their asymptotic behavior in various settings (as H goes to 0, H goes to 1, T grows large, a goes to 0 etc. ); see, e.g., [21,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of the work is focused on finding upper and lower bounds for these quantities (see, e.g. [35,12,10,4,7,8,5]) or determining their asymptotic behavior in various settings (as H goes to 0, H goes to 1, T grows large, a goes to 0 etc. ); see, e.g., [21,5].…”
Section: Introductionmentioning
confidence: 99%
“…A problem related to the asymptotic behavior of H α − H δ α was considered in [6,7], who have shown that E sup t∈[0,1] B α (t) − E sup t∈[0,1] δ B α (t), decays like δ α/2 up to logarithmic terms. We should emphasize that in Theorem 2.1, case α ∈ (0, 1) we were able to establish that the upper bound for the discretization error decays exactly like δ α/2 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the estimation of M H (T, a) is so challenging, many works are dedicated to finding its theoretical upper and lower bounds. The most up-to-date bounds for M H (T, 0) can be found in [8,9], see also [23,26] for older results. The most up-to-date bounds for M H (∞, a) can be found in [4].…”
Section: Introductionmentioning
confidence: 99%